Studi Analisis Zat Gizi Biskuit Fungsional Subtitusi Tepung Kelor dan Tepung Ikan Gabus - Evi Setyawati; Nurasmi Nurasmi; Irnawati Irnawati (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; One of the local ingredients in Sigi Regency is Moringa (Moringa oleifera) and Fish Gabus (Channa striata). Destination; produced PMT-P biscuits by substituting Moringa flour and snakehead fish meal and analyzed their nutritional content. Method; This type of research is pure experimental with 5 treatment formulas 0%, 20%, 40%, 60%, and 80%. Data analysis using the Kruskal-Wallis test. The physical properties test used the hedonic model organoleptic test and the proximate level test. Result; that the formula has a brownish-green color, smells slightly of Moringa leaves and snakehead fish, sweet taste, and crunchy texture. Water Content 0.6929%, Ash Content 1.862%, Protein 26.69%, Carbohydrates 18.5 mg / 100g, Fat 31.422%. Vitamin A 10.22 µg / 100 gr, Vitamin C 3.128.8 mg / 100gr, Iron 2.108 mg / 100gr, Calcium 7.403 mg / 100gr, Phosphorus 151.331 mg / 100gr, Zinc 9.5 mg / 100gr, Sodium 361.339 mg / 100gr. Conclusion; functional biscuit products made from Moringa flour and snakehead fish meal have met the SNI standard requirements and supplementary feeding (PMT) for pregnant women